Comparison between Transtibial Versus Anteromedial Portal Femoral Tunnel Drilling Technique in Arthroscopic Anterior Cruciate Ligament Reconstruction with Hamstring Autograft: A Comparative Study - Israr Ahmad, Behzad Manzoor, Amjad Maqsood, Zahid Habib Qureshi, Muhammad Badar-Ud-Din Zafir, Alisha Raza Qureshi, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The most common ligament damage pertaining to the knee joint is an anterior cruciate ligament (ACL) injury. The independent drilling approach is now the primary emphasis for femoral tunnel preparation, rather than the transtibial technique (TT). Objective: To determine the anteromedial portal's mean Lysholm score with TT for the femoral tunnel drilling technique used in hamstring autograft-assisted ACL repair. Material and methods: In the Department of Orthopaedic Surgery at the Ibne Sina Hospital and Research Institute in Multan, Pakistan, a comparative research was carried out. Total duration of this study was two years. (from 10th dec 2020 to 10th dec 2022) .A total number of 60 patients were taken using random sampling technique ( divided into group A which was TT technique, and group B which was Am technique. Baseline characteristics which includes BMI, weight, age, height, gender, as well as side of injury were noted. By using knee range of motion along with the Lysholm score, the functional outcome was evaluated six months after surgery. Results: The participants' average age was 30.9 ± 5.2 years. There were 66.7% males. Fall injuries were the most frequent type which was 38.3%, after the sports (33.3%). Mean Lysholm score of the participants was 93.7 ± 2.4. Mean Lysholm score of participants in Anteromedial portal group was significantly higher compared to trans-tibial approach (95.3 ± 2.0 vs. 92.1 ± 1.7, p-value < 0.001). However, hospital stay and knee range of movements did not noticeably differ in both the sets (p-value > 0.05). Conclusion: Our study concluded that AMP technique is better compared to TT technique in the terms of mean lysholm score post-operatively. Keywords: Anterior cruciate ligament reconstruction, Lysholm Knee Score, Knee injuries